2020
DOI: 10.1073/pnas.1922755117
|View full text |Cite
|
Sign up to set email alerts
|

Contractile pericytes determine the direction of blood flow at capillary junctions

Abstract: The essential function of the circulatory system is to continuously and efficiently supply the O2 and nutrients necessary to meet the metabolic demands of every cell in the body, a function in which vast capillary networks play a key role. Capillary networks serve an additional important function in the central nervous system: acting as a sensory network, they detect neuronal activity in the form of elevated extracellular K+ and initiate a retrograde, propagating, hyperpolarizing signal that dilates upstream a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
202
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(223 citation statements)
references
References 46 publications
14
202
1
Order By: Relevance
“…Pericytes that positively express α-SMA regulated CBF, protecting downstream capillaries from elevated perfusion pressure and limiting vasodilation. These cells particularly play a vital role in the regulation of CBF and blood distribution when they localized at the proximal bifurcations of PAs of capillaries [43], which was consistent with a recent report by Gonzales et al, in mice retinal arterioles and capillaries [42,47] and by our group in cerebral microvessels in rats [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pericytes that positively express α-SMA regulated CBF, protecting downstream capillaries from elevated perfusion pressure and limiting vasodilation. These cells particularly play a vital role in the regulation of CBF and blood distribution when they localized at the proximal bifurcations of PAs of capillaries [43], which was consistent with a recent report by Gonzales et al, in mice retinal arterioles and capillaries [42,47] and by our group in cerebral microvessels in rats [31].…”
Section: Discussionsupporting
confidence: 92%
“…It has been well established that cerebral VSMCs play an essential role in the regulation of the myogenic response and autoregulation in the cerebral circulation [6,37,38]. More recently, emerging evidence indicated that cerebrovascular pericytes expressing alphasmooth muscle actin (α-SMA) that primarily localize on precapillary arterioles also participate in controlling CBF and maintaining cerebral vascular function with their contractile capability [39][40][41][42][43][44][45][46][47][48][49][50]. However, whether 20-HETE directly constricts cerebrovascular pericytes and precapillary arterioles and whether it is related to CBF autoregulation in the deep brain cortex have never been studied.…”
Section: -Hydroxyeicosatetraenoic Acidmentioning
confidence: 99%
“…Beyond this point in the vasculature, mural cells do not express high levels of α-SMA, although one recent study suggested that retinal mural cells retain expression of a low level of this protein (Alarcon-Martinez et al, 2018) and they do express very low levels of the Acta2 gene in the brain (He et al, 2018;Vanlandewijck et al, 2018). As a result, these cells are not equipped to regulate vessel diameter over abrupt time scales, but there is clear evidence that they may contract slowly under certain circumstances (reducing the diameter of the underlying vessel by up to ∼25%; Fernández-Klett et al, 2010;Gonzales et al, 2020). Thus, we consider the relatively static diameter vessels downstream of the α-SMA terminus (which typically occurs between the 1st and 4th order branch in immunostaining experiments; Grant et al, 2019) to be capillaries.…”
Section: Mural Cell Properties Transition Gradually With Increasing Bmentioning
confidence: 99%
“…However, the vasculatures in both retina and cortex respond similarly to neuronal activity with elevations in blood flow (Newman, 2013), and similar mechanisms underpinning these responses appear to be at play in either bed. K + , PGE 2 , and EETs, for example, have been implicated in control of blood flow in both circulations (Newman, 2013;Longden et al, 2017;Gonzales et al, 2020). Recent studies have also indicated the utility of non-invasive examinations of the retinal vasculature as a marker for detecting cerebrovascular diseases, due to a similar susceptibility of both circulations to vascular risk factors such as hypertension or diabetes (Patton et al, 2005;van de Kreeke et al, 2018;McGrory et al, 2019;Querques et al, 2019).…”
Section: Box 2 | a Brief Comparison Of Retinal And Brain Vasculaturesmentioning
confidence: 99%
See 1 more Smart Citation